Interplay between sympathetic nervous system and inflammation in aseptic loosening of hip joint replacement. Issue 1 (December 2018) - Ribeiro-da-Silva, M.; Vasconcelos, D.; Alencastre, I.; Oliveira, M.; Linhares, D.; Neves, N.; Costa, G.; Henrique, R.; Lamghari, M.; Alves, C.
Abstract Inflammation is a common symptom in joint disorders such as rheumatoid arthritis, osteoarthritis (OA) and implant aseptic loosening (AL). The sympathetic nervous system is well known to play a critical role in regulating inflammatory conditions, and imbalanced sympathetic activity has been observed in rheumatoid arthritis. In AL it is not clear whether the sympathetic nervous system is altered. In this study we evaluated the systemic and local profile of neuroimmune molecules involved in the interplay between the sympathetic nervous system and the periprosthetic inflammation in hip AL. Our results showed that periprosthetic inflammation does not trigger a systemic response of the sympathetic nervous system, but is mirrored rather by the impairment of the sympathetic activity locally in the hip joint. Moreover, macrophages were identified as key players in the local regulation of inflammation by the sympathetic nervous system in a process that is implant debris-dependent and entails the reduction of both adrenergic and Neuropetide Y (NPY)-ergic activity. Additionally, our results showed a downregulation of semaphorin 3A (SEMA3A) that may be part of the mechanism sustaining the periprosthetic inflammation. Overall, the local sympathetic nervous system emerges as a putative target to mitigate the inflammatory response to debris release and extending the lifespan of orthopedic implants.